The Determinants of Family Support on Management of nausea and Vomiting in Chemotherapy Patientes with cervical cancer in Singkarak Room of RSUD dr. saiful Anwar east Java Provincial Goverment - Rosario Hylde; Nicky Danur Jayanti Danur Jayanti; Yuniar Angelia Puspadewi (LPPM Widyagama Husada Malang, 2025)
ABSTRACT Hylde, Rosario Gillberta. 2024. Determinants of Family Support on Management of Nausea and Vomiting in Chemotherapy Patients with Cervical Cancer in Singkarak Room of RSUD. dr. Saiful Anwar East Java Provincial Government. Thesis. S1 Midwifery Study Programme Widyagama Husada College of Health Sciences Malang. Advisors: 1. Nicky Danur J, S. ST., M. KM., 2. Yuniar Angelia P, S. SiT., M. Kes. Family support as the main caregiver in the incidence of nausea and vomiting in chemotherapy patients with cervical cancer has a significant impact on patients while undergoing chemotherapy. The purpose of this study is to determine what the determinants in family support for the creation of management of nausea and vomiting in chemotherapy patients with cervical cancer in the Singkarak Room, RSUD dr. Saiful Anwar Malang are. This research was evidence-based research and used respondents taken by total sampling of 35 people. This research design was descriptive quantitative with a cross sectional approach. The research instrument used was a questionnaire with previous validity and reliability tests. Data analysis used univariate analysis and used Kendall's Tau test for bivariate analysis. Based on the research that has been done, it is found that the test between the independent variables on the dependent variable is obtained in the age variable p-value 0.004 and r-value -0.448, education variable p-value 0.003 and r-value -0.478, income variable p-value 0.000 and r-value -0.702, variable level of knowledge p-value 0.000 and r-value -0.679, which means it has a significant relationship with a weak correlation. It can be concluded that the determinants of nausea and vomiting management in chemotherapy patients with cervical cancer provide an overview of how the role and family support for chemotherapy patients with nausea and vomiting are very influential. It is expected that family support can be optimized when accompanying patients undergoing chemotherapy. Reference: 48 References (2006-2023)Keywords: nausea and vomiting, cervical cancer, family support.